The Ambivalent Relation to Faith in Elin Pelin’s Storiesof the Early 20th Century - Bonov, Yonko (Forum Theologicum Sardicense, 2025)
Yonko Bonov (Doct. candidate at the Theological Faculty of Sofia University) The Ambivalent Relation to Faith in Elin Pelin’s Stories of the Early 20th Century In his stories written during the first five years of the 20th century, Elin Pelin presents an ambivalent attitude toward the Christian faith and the clergy who profess it. Although Elin Pelin is not a church writer, he accurately depicts the lives of people whose actions are deeply influenced by living Orthodox faith. Even in situations of impasse and profound suffering that separate individuals from society, faith remains in their hearts and souls. This suffering often leads to a deeper connection with the Lord, even in moments of apparent denial. For a Bulgarian, God is always perceived as a personal and immediate helper, in whose name people uphold and follow their ethical values. This faith, though sometimes expressed in a primitive and imperfect manner, remains accessible and meaningful to the people. Elin Pelin’s literary merit lies in his ability to capture in her vibrant prose the motives and imperfections present in the practical confession of Orthodox faith among Bulgarians.